The effect of extrusion arc groove on the fatigue life of wing panel with functional holes: Experiment and simulation. (November 2022) - Sun, Yifang; Grebenikov, A.G.; Li, Chenghu
Highlights: The lifetime of wing panel with hole can be extended by extruding the arc groove. The lifetime is affected by the depth and angle of the extrusion arc groove. There are optimal values for the depth and angle of the extrusion arc groove. The lifetime can be increased by more than 2.34 times with the optimal arc groove. Abstract: In this paper, the study of the effect of the extrusion arc groove on the fatigue life of a wing panel with functional holes is carried out to solve the problem that the fatigue life of the wing panel is reduced due to the functional holes. The influences of the depth and angle of the extrusion arc groove on the fatigue life of the wing panel are studied by means of experiment and finite element simulation. The results show that: For the wing panel with functional holes, the fatigue life can be extended by the extrusion arc grooves, which is due to the residual stress is generated after extrusion process, that counteracts the part of the effect of the load, so that the characteristic stress is reduced. The fatigue life of the wing panel with functional holes is affected by the depth of the extrusion arc grooves. When the depth is 0–0.15 mm, the fatigue life is extended slightly; when the depth is 0.15–0.3 mm, the fatigue life is greatly extended; when the depth is more than 0.3 mm, the fatigue life is extended slowly. The fatigue life of the wing panel with functional holes is also affected by the angle of the extrusion arc grooves. The fatigue life is extended with the increase of the angle until the angle reaches the optimal angle 120°. The fatigue life of the studied wing panel can be extended by more than 2.34 times with the optimal extension arc grooves.